If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = 9(-6x) Remove parenthesis around (-6x) -4 = 9 * -6x Multiply 9 * -6 -4 = -54x Solving -4 = -54x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '54x' to each side of the equation. -4 + 54x = -54x + 54x Combine like terms: -54x + 54x = 0 -4 + 54x = 0 Add '4' to each side of the equation. -4 + 4 + 54x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 54x = 0 + 4 54x = 0 + 4 Combine like terms: 0 + 4 = 4 54x = 4 Divide each side by '54'. x = 0.07407407407 Simplifying x = 0.07407407407
| 8+7n=42 | | 5x+6y=-11 | | -9+9y+3-2y= | | 2x(x-2)+20=9 | | 3-3=13y-8-12y | | 2(-3b)+4b=-4 | | 6(8m+11)=9(2m-23) | | 3=-3x+3 | | y=-4(0)+3 | | 10z+4=10z+4 | | 85-7x=38x+20 | | 5=-4x+5 | | 13-7x=73-21x | | -27-7x=9x+21 | | 6x+10=130-6x | | 57-2x=7x+21 | | -9.2x-16.2=3.4x+53.1 | | f(y+p)f(y)=-5y+9 | | 10x-2=8+14 | | f(y)=-5y+9f(y+p) | | 9=7x+16*8 | | 5x=8x-7z | | f(y)=-5y+9 | | 14x+2y=10 | | x+(x+3)+(x-3)+(x*3)=95 | | 0.4x+0.1666666667=1 | | 4.5x+3=3.5x | | f(z)=4z^2+5z-5 | | -8x^2+21x=0 | | 6x-3x+2x=20 | | 9=7x+16 | | -3=5xk+7 |